Effect of common vegetables extracts on lipid and glucose in 3t3-l1 adipocytes - Sassi, Assia; Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher (2015)
Introduction: Obesity is the major health problem both in developing and developed countries and Malaysia is no exception. Due to obesity, various adverse health conditions such as diabetes mellitus (DM), metabolic syndrome (MS) and cardiovascular diseases (CVDs) are frequently inborn. The prevalence’s of the listed diseases are increasing at alarmingly higher rates in the world including Malaysia. The treatment cost is increasing exponentially therefore; prevention would be the better option to fight against these diseases. Materials and Methods: Three common vegetables namely Momordica Charantia (also known as Bitter gourd, Karela or Peria Katak), LagenariaSiceraria (known as Bottle Gourd, Calabash) and TrichosanthesCucumerina (known as Snake gourd or LabuUlar) of the Cucurbitaceae family were investigated for their water and ethanolic extracts (extracted from whole vegetable, peels and seeds) effect on 3T3-L1 adipocytes were assessed on cell differentiation, adipogenesis, adipolysis (using appropriate kits) and on glucose uptakes (assessed by radioisotopes). Results: The cells tolerated a concentration up to 0.063 mg/ml of extracts. The cell upon treatment demonstrated reduced lipid accumulation in the cells. The water and ethanol extracts showed reduction in lipid accumulation which is evident from reduced adipogenesis in the treated cells. Bitter gourd and Snake gourd seeds and Bottle Gourd peels & seeds of the ethanolic extract showed highest inhibition/reduction of adipogenesis. Lipolysis was enhanced when the adipocytes were treated with ethanolic extracts of the whole and peel from the three sources of vegetables. Furthermore, there was improved glucose uptake in the extract treated cells. Conclusion: The results of this study suggest that these vegetable can be useful for the prevention of obesity and also may provide better regulation over glucose metabolism.